RANCANG BANGUN APLIKASI DIAGNOSA TES KEJIWAAN BERBASIS WEB MENGGUNAKAN METODE MINI-MENTAL STATE EXAMINATION (MMSE) - Iqbal Hanafi, Muhamad; Susanti, Deffy (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
In the current era of globalization, the rapid development of science and technology makes us in activities, the technology needed to achieve better results more efficiently, internet technology can be used to facilitate and facilitate information sources in the health sector. Utilization and use of the development of current computer technology in science, which consists of various branches of science, one of which is in the branch of Psychology. Psychology about the importance of knowledge about humans, seeing this can be seen knowledge about science is very broad and does not discuss about the use of technology involved in it. In the process of collecting data from this study using two methods of library methods. The system built is a web-based psychiatric expert diagnosis system using a mental state examination method. This system has the function to activate psychiatric illnesses, so that the existing system can be more easily and effectively.